Taxation of capital gains of companies from the alienation of shares - Popović Dejan; Ilić-Popov Gordana (Anali Pravnog Fakulteta u Beogradu)
The paper deals with the tax treatment of capital gains on shares of companies both in national and tax treaty law. The authors indicate that the authentic interpretation of the Art. 27 of Serbia's Tax on Profits of Legal Entities Law opens the door to taxing not only realised but also potential capital gains thus triggering certain harmful consequences. Relying on the comparative legal analysis they suggest measures how to eliminate the existing economic double taxation and plead for granting a credit for the tax on capital gains paid abroad. In order to hamper tax evasion the introduction of a security for the resident company whose shares are alienated by a non-resident company at a gain is suggested whenever the tax return has not been filed. By analysing Serbia's 58 tax treaties the authors conclude that 28 of them contain a single demarcation rule exclusively granting jurisdiction to tax the capital gains on shares to the state of residence of the alienator, while in remaining 30 treaties an additional anti-avoidance rule is prescribed.